A Full-Scale Experimental Study of the Vertical Dynamic and Static Behavior of the Pier-Cap-Pile System - Jianlei Liu; Meng Ma (Advances in Civil Engineering)
The bearing capacity evaluation of bridge substructures is difficult as the static loading test (SLT) cannot be employed for the bridges in services. As a type of dynamic nondestructive test technique, the dynamic transient response method (TRM) could be employed to estimate the vertical bearing capacity when the relationship between static stiffness and dynamic stiffness is known. The TRM is usually employed to evaluate single piles. For the pier-cap-pile system, its applicability should be investigated. In the present study, a novel full-scale experimental study, including both TRM test and SLT, was performed on an abandoned bridge pier with grouped pile foundation. The test included three steps: firstly, testing the intact pier-cap-pile system; then, cutting off the pier and testing the cap-pile system; finally, cutting off the cap and testing the single pile. The TRM test was repeatedly performed in the above three steps, whereas the SLT was only performed on the cap-pile system. Based on the experimental results, the ratio of dynamic and static stiffness of the cap-pile system was obtained. The results show that (1) in the low-frequency range (between 10 and 30 Hz in this study), the dynamic stiffness of the whole system is approximately four times of that of a single pile; (2) the ratio of dynamic and static stiffness of the cap-pile system tested in the study is approximately 1.74, which was similar to other tested values of a single pile; (3) to evaluate the capacity of similar cap-pile system and with similar soil layer conditions by TRM, the value of Kd/Ks tested in the study can be used as a reference.